The feasibility of forming a monetary union in SADC : meeting convergence and optimum currency area criteria and evaluating fiscal sustainability - Mokoena, Motshidisi Suzan (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2013)
In conformity with the goal of the African Union to build a monetary union for the entire African continent, one of the goals of the Southern African Development Community (SADC) is the formation of a monetary union with a single central bank. Towards this end certain macroeconomic convergence criteria, which are closely aligned with those used by the European Union (EU), have been set. While empirical research on whether or not SADC would benefit from the formation of a currency union has focused on the optimum currency area criteria, no reference to these criteria is made in the SADC programme. Instead, the SADC approach has been governed by a set of macroeconomic convergence criteria synonymous with those pursued by the European Monetary Union (EMU) prior to its formation. Doubts regarding the future of the EU have recently been raised as a result of debt crises in certain member states, implicitly raising questions about the adequacy of the convergence criteria that were adopted. Accordingly, this study considers the feasibility of establishing a currency union in the SADC region. The proposed convergence criteria are assessed against the theory of optimum currency areas as well as in terms of their adequacy in the light of recent EU experience. In addition, the paper provides a preliminary assessment of the fiscal sustainability of the SADC region by conducting Engle-Granger cointegration tests on the public debt and revenue series for the SADC countries under analysis. It was observed that SADC has made considerable progress towards meeting its macroeconomic convergence criteria in recent years. However, in light of the regions' heavy dependence on commodity exports coupled with recent price fluctuations in this regard, the sustainability of this progress is questioned. Furthermore, a review of the EMU experience to date highlights numerous flaws in its approach and the potential challenges the SADC region should consider in moving forward with its agenda. In essence, the study suggests that almost all the SADC member states are fiscally unprepared for monetary union formation and the recent EMU debt crisis has highlighted the importance of acquiring a state of fiscal sustainability prior to union formation. In addition, it is imperative that the SADC members continue to address issues of product diversification, intraregional trade and political unification, all of which should be governed by a centralised fiscal authoriry.
Keywords: Southern African Development Community; Economic and Monetary Union; Common Monetary Area (Organization); Economic policy -- Africa, Southern; Monetary policy -- Africa, Southern; Monetary unions